Oligodendrocytes Support Neuronal Glutamatergic Transmission via Expression of Glutamine Synthetase - Xin, Wendy (Cell Rep, 2019)
Glutamate has been implicated in a wide range of brain pathologies and is thought to be metabolized via the astrocyte-specific enzyme glutamine synthetase (GS). We show here that oligodendrocytes, the myelinating glia of the central nervous system, also express high levels of GS in caudal regions like the midbrain and the spinal cord. Selective removal of oligodendrocyte GS in mice led to reduced brain glutamate and glutamine levels and impaired glutamatergic synaptic transmission without disrupting myelination. Furthermore, animals lacking oligodendrocyte GS displayed deficits in cocaine-induced locomotor sensitization, a behavior that is dependent on glutamatergic signaling in the midbrain. Thus, oligodendrocytes support glutamatergic transmission through the actions of GS and may represent a therapeutic target for pathological conditions related to brain glutamate dysregulation.